Quiet riot : the culture of teaching and learning in schools - Hoffman, Diane M., 1954- (Rowman & Littlefield Publishers, 2016)
"Quiet Riot offers an anthropological critique of teaching and learning in two U.S. high schools over a twenty-seven year period. Based on the author's experiences shadowing two average students in 1983 and 2009, it presents detailed observations that powerfully capture the reality of student experiences in school"--